The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21470/1678-9741-2020-0357
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124a Protects the Myocardium Against Ischemia Reperfusion Injury Through Regulation of the Notch Signaling Pathway

Abstract: Introduction This study’s objective is to investigate the effect of downregulation of micro ribonucleic acid (miR)-124a on myocardial injury after ischemia reperfusion (I/R) in rats. Methods Sprague Dawley (SD) rats (n=20) were divided into four groups - sham, I/R, I/R+miR-124a antagomir (I/R+ant-miR-124a), and I/R+ant-normal control (NC). The pathomorphological and infarct size variance of injured myocardial tissues with IR were conducted with hematoxylin (HE) and trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies investigated whether the Notch signaling-induced proangiogenic effect may be the reason for the beneficial effect after the treatment of MI using traditional Chinese medicine and cell therapy 62,133,[140][141][142][143][144][145] . Many studies have reported that the regulation of non-coding RNAs including miRNAs 123,[146][147][148][149][150][151][152][153][154] , lncRNAs 155,156 , and circRNAs 147 could exert a therapeutic role in myocardial repair. Moreover, some drugs are reported to correlate with the Notch pathway [157][158][159][160][161] .…”
Section: Notch Signaling Pathway In MImentioning
confidence: 99%
“…Previous studies investigated whether the Notch signaling-induced proangiogenic effect may be the reason for the beneficial effect after the treatment of MI using traditional Chinese medicine and cell therapy 62,133,[140][141][142][143][144][145] . Many studies have reported that the regulation of non-coding RNAs including miRNAs 123,[146][147][148][149][150][151][152][153][154] , lncRNAs 155,156 , and circRNAs 147 could exert a therapeutic role in myocardial repair. Moreover, some drugs are reported to correlate with the Notch pathway [157][158][159][160][161] .…”
Section: Notch Signaling Pathway In MImentioning
confidence: 99%
“…Accumulated studies have assured the crucial micrornas (mirnas) and their target genes in controlling i/r damage in animal or cell models [ 11 , 12 ]. Meanwhile, mirnas can also influence organ damage after sev treatment via modulating associated pathways.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 For example, miR-21, miR-124 and miR-182-5p were reported to regulate MI/R injury. [15][16][17] The expression of miR-23a-5p was significantly enhanced during myocardial infarction. 18 However, miR-23a-5p has been poorly studied in heart-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRNAs) are members of noncoding RNAs, which play important roles in MI/R injury 13,14 . For example, miR‐21, miR‐124 and miR‐182‐5p were reported to regulate MI/R injury 15–17 . The expression of miR‐23a‐5p was significantly enhanced during myocardial infarction 18 .…”
Section: Introductionmentioning
confidence: 99%